Digital Transformation: Optimizing the Regional Tax Audit Process Using the Data Analytics System - Reinaldi Simba, Ahmad (Iapa Proceedings Conference, 2024)
The regional tax audit process often faces challenges, such as limited data, time inefficiency, and potential errors in decision making. Therefore, digital transformation using a data analytics system is important to optimize the regional tax audit process. This paper presents how digital transformation in the regional tax audit process using a data analytics system must be carried out. The method used is qualitative descriptive to explain in detail the digital transformation in the regional tax audit process using a data analytics system. The results of the study show that this digital transformation is very necessary in the implementation of regional tax audits. The implementation of a data analytics system will be able to minimize the risk of errors, increase efficiency, accuracy and precision of taxpayer information, transparency, and can provide data-based recommendations that will facilitate and strengthen decision making. This visualization helps in presenting audit results effectively and making decision making faster and more precise